Respuesta :

Simplifying

2x + -7 = 3x + 5

Reorder the terms:

-7 + 2x = 3x + 5

Reorder the terms:

-7 + 2x = 5 + 3x

Solving

-7 + 2x = 5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-7 + 2x + -3x = 5 + 3x + -3x

Combine like terms: 2x + -3x = -1x

-7 + -1x = 5 + 3x + -3x

Combine like terms: 3x + -3x = 0

-7 + -1x = 5 + 0

-7 + -1x = 5

Add '7' to each side of the equation.

-7 + 7 + -1x = 5 + 7

Combine like terms: -7 + 7 = 0

0 + -1x = 5 + 7

-1x = 5 + 7

Combine like terms: 5 + 7 = 12

-1x = 12

Divide each side by '-1'.

x = -12

Simplifying

x = -12

ACCESS MORE